Empiric Treatment of Focal Organizing Pneumonia in a Patient with a Low-Risk Lung Mass. (30th July 2013) - Alikhan, Mir; Veeraraghavan, Srihari
Abstract : The authors present a case of a 57-year-old man presenting with a solitary lung mass. Transbronchial biopsy showed an organizing pneumonia pattern. A therapeutic trial of corticosteroids resulted in complete resolution avoiding surgery. The authors discuss the diagnosis of focal organizing pneumonia without surgical resection.